Il Cristianesimo in Giappone. Tradizioni nascoste e il coraggio per la fede - Olimpia Niglio; Paolo Giulietti (Antropologia e Teatro, 2023)
The difficult path of the missionary worksite, which since the 13th century has seen mainly the mendicant orders, and in particular the Franciscans, Dominicans and Augustinians, active, played a fundamental role in spreading the Gospel to the then known world. This path, also marked by mercantile routes, had particularly difficult experiences when it encountered the lands of the East and especially Japan. These experiences marked the lives of many Western missionaries who came to the lands of Japan, giving rise to a cultural heritage that for more than three centuries remained hidden. This heritage today constitutes an important reference for reflecting on the value of faith and the important presence of the Church in society for a fruitful dialogue between the diversities.